What's Up With Stock Prices? An Empirical Study of Financial Performance and Company Scale Indexed in LQ45 During 2019-2022 - Viki Riko Felandi; Mahameru Rosy Rochmatullah (Yayasan Riset dan Pengembangan Intelektual, 2024)
The aim of this study is to analyze the influence of Debt to Equity Ratio, Earnings Per Share, Net Profit Margin, Net Income, and Company Size on the companies indexed in the LQ45 in Indonesia from 2019 to 2022. This research utilizes secondary data with a population comprising 58 companies indexed in the LQ45 in Indonesia during the years 2019-2022. The technique employed is purposive sampling with the multiple linear regression analysis method. The results of this study indicate that, partially, Debt to Equity Ratio and Net Profit Margin do not significantly influence the companies indexed in the LQ45 in Indonesia from 2019 to 2022. However, Earnings Per Share, Company Size, and Net Income significantly influence the companies indexed in the LQ45 in Indonesia from 2019 to 2022.